2007
DOI: 10.1111/j.1600-0447.2006.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between antenatal depression and low birthweight in a developing country

Abstract: Objective:  There is a high prevalence of depression in south Asian women. We aimed to examine the association between antenatal depression and low birthweight (LBW) in infants in a rural community in Rawalpindi, Pakistan. Method:  A total of 143 physically healthy mothers with ICD‐10 depression in the third trimester of pregnancy and 147 non‐depressed mothers of similar gestation were followed from birth. Infant weight was measured and information collected on socioeconomic status, maternal body‐mass index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
4
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(195 citation statements)
references
References 22 publications
(29 reference statements)
12
163
4
16
Order By: Relevance
“…with those of Rahman et al (9) and the different questionnaires used to assess anxiety as compared with the Generation R Study (23).…”
Section: Prenatal Stress and Fetal Growthmentioning
confidence: 94%
See 1 more Smart Citation
“…with those of Rahman et al (9) and the different questionnaires used to assess anxiety as compared with the Generation R Study (23).…”
Section: Prenatal Stress and Fetal Growthmentioning
confidence: 94%
“…In animal research, prenatal stress has been related to lower fetal and birth weight of the offspring (7,8). In humans, results of research investigating the relationship between maternal distress and lower birth weight are inconsistent (9)(10)(11)(12)(13)(14). Although there is evidence that maternal stress during pregnancy can lead to slower fetal growth, the variance explained by maternal stress is very low, i.e., about 1% in a meta-analysis of 35 studies (15).…”
mentioning
confidence: 99%
“…36 A study conducted in France with 634 pregnant women concluded that anxiety and depression symptoms, combined with specific biomedical factors, were associated with spontaneous preterm birth. 37 In Brazil, a longitudinal cohort study conducted in the city of Jundiaí, state of São Paulo, found an association between stress during pregnancy and the variables low birth weight and preterm birth.…”
Section: Positive Resultsmentioning
confidence: 99%
“…Variables such as smoking cigarettes, drinking alcohol and chewing Khat are less socially acceptable and thus prone to social desirability bias [30][31][32][33].…”
Section: Limitationsmentioning
confidence: 99%